Pengaruh Corporate Governance, Growth Opportunity dan Net Profit Margin (NPM) Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Go Public di Bursa Efek Indonesia Tahun 2008-2011) - Tikawati Tikawati (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This study examines the effect of corporate governance, growth opportunity, and net profit margin (NPM) to the firm value with firm size as a control variable. Corporate governance is proxied by the survey results CGPI (CG Index), growth opportunity is measured by the ratio of stock market value to book value of the share capital, while net profit margin is measured with ratio of net income to sales. Firm size used in this study is the log of total assets. This study uses secondary data from ICMD and IDX. Using analysis this study find that corporate governance, growth opportunity, and net profit margin positively and significantly effect the firm value.